Implications of Skill-Biased Technological Change: International Evidence* - Berman, Eli; Bound, John; Machin, Stephen (Quarterly Journal of Economics, 1998)
Demand for less-skilled workers plummeted in developed countries in the 1980s. In open economies, pervasive skill-biased technological change (SBTC) can explain this decline. SBTC tends to increase the domestic supply of unskill-intensive goods by releasing less-skilled labor. The more countries experiencing a SBTC, the greater its potential to decrease the relative wages of less-skilled labor by increasing the world supply of unskill-intensive goods. We find strong evidence for pervasive SBTC in developed countries. Most industries increased the proportion of skilled workers despite generally rising or stable relative wages. Moreover, the same manufacturing industries simultaneously increased demand for skills in different countries. Many developing countries also show increased skill premiums, a pattern consistent with SBTC.